2015
DOI: 10.17159/0379-4350/2015/v68a13
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the oxidation of Coomassie Brilliant Blue-R dye by hypochlorite and role of acid therein

Abstract: The kinetics of the oxidation of a triphenylmethane dye, Brilliant Blue-R (BB -Na + ), in aqueous solution by hypochlorite as a func-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…As water is present in the reaction mixture in a large excess as compared with the amount of intermediate A , the reaction is proposed to follow pseudo-first-order kinetics. The pseudo-first-order kinetics behavior of hypochlorite was also observed by other researchers. …”
Section: Resultssupporting
confidence: 77%
“…As water is present in the reaction mixture in a large excess as compared with the amount of intermediate A , the reaction is proposed to follow pseudo-first-order kinetics. The pseudo-first-order kinetics behavior of hypochlorite was also observed by other researchers. …”
Section: Resultssupporting
confidence: 77%
“…45,46 Dyes have been shown to degrade to small chlorinated organic compounds with molar masses as low as 234 g/mol and with a less branched structure compared to the original dye. 47,48 Similarly, natural organic matter, such as humic acid, has exhibited ring-opening reactions and degradation to low molecular weight trihalomethanes such as chloroform (MW = 119.4 g/mol) under chlorinating conditions. 46,49 Based on the degradation of these organic foulants into smaller byproducts, the observed improvement in permeance following hypochlorite treatment can be attributed to the degradation of the previously adsorbed organic material from within the GO galleries of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Cleaning with 100 ppm of hypochlorite exhibits permeance recoveries of 90.3, 98.2, and 94.6% for membranes fouled with MB, TA, and BSA, respectively. There is no doubt that the oxidizing capacity of this reagent is the primary factor for the excellent permeance recovery, but the role of the ionic strength of the hypochlorite solution cannot be neglected, as it can result in changed electrostatic interactions at the adsorbed foulant–membrane interface and deliver a positive contribution to the removal of foulants from the membrane surface. , Such effects have been attributed to a variety of reasons including the increase in the hydration repulsion forces between the membrane and foulant molecules, which decreases the adsorption and deposition of foulants on the membrane surface. Alternatively, the improvement could also be attributed to the breakdown of the organic foulant into smaller byproducts that can be easily removed from the membrane by rinsing or permeating through the GO membrane. , Dyes have been shown to degrade to small chlorinated organic compounds with molar masses as low as 234 g/mol and with a less branched structure compared to the original dye. , Similarly, natural organic matter, such as humic acid, has exhibited ring-opening reactions and degradation to low molecular weight trihalomethanes such as chloroform (MW = 119.4 g/mol) under chlorinating conditions. , Based on the degradation of these organic foulants into smaller byproducts, the observed improvement in permeance following hypochlorite treatment can be attributed to the degradation of the previously adsorbed organic material from within the GO galleries of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The observed fractional order reaction for [H + ] indicates that acid may not be directly participating in the rate-determining step. [40] It was reported that different oxybromo species (HBrO 3 , H 2 BrO 3 + and BrO 2…”
Section: Effect Of Acid Concentrationmentioning
confidence: 99%
“…The plot of lnk obs vs ln[H + ] in Figure 6 is linear with a slope of 0.27 (R 2 =0.9875). The observed fractional order reaction for [H + ] indicates that acid may not be directly participating in the rate‐ determining step [40] . It was reported that different oxybromo species (HBrO 3 , H 2 BrO 3 + and BrO 2 + ) exist in the solution depending on the pH of the medium, which competes with BrO 3 − in the oxidation of dye [27] …”
Section: Introductionmentioning
confidence: 99%